OVARY AND UTERINE RNA/DNA RATIO IN VARIOUS REPRODUCTIVE CONDITIONS OF FEMALE WHITE RAT (Rattus norvegicus) - Livana Dethris Rawung; Kasiyati (Indonesian Biodiversity Journal, 2020)
RNA / DNA ratio is a parameter that shows the activity of protein synthesis that is taking place in a cell. In mammals, during the reproductive period, the ovaries and uterus are the organs that play an active role. The purpose of this study was to know the activity of protein synthesis that occurs in the ovaries and uterus in female white rats (Rattus norvegicus) in various physiological conditions during reproduction. In this study, female rats that were sexually mature were used. Data were collected on rats with physiological status not yet pregnant (T0); pregnancy 10 and 20 days (T10, T10), and lactation 7, 10, and 20 days (L7, L10, L20). The results showed that there was a decrease in the value of the ovary RNA / DNA ratio during pregnancy and lactation. In contrast, the uterine RNA / DNA ratio increases during pregnancy and lactation. Based on the results of the study, it can be concluded that the increase in the uterine RNA: DNA ratio that occurs during pregnancy is because it is used for the synthesis of various structural and functional components for fetal growth and development